HAK DAN KEWAJIBAN MAKELAR DALAM PERJANJIAN DAGANG - Delha Saputra Asuntya, Dewa Made; Dunia, Ngakan Ketut; Rudy, I Dewa Gede (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 01, Februari 2014, 2014)
Middleman rights and obligations in agreement of trade, its problem how rights and obligations a middleman in agreement of its. Type research trade is type research of law of normatif. Bearing with research of this skripsi utilized approach of legislation, approach of fact, and approach of law concept analysis. Law materials the used materials punish primary, materials punish sekunder, and tertiary law materials. Law materials collected to pass/through documentation study. Technique analyze law materials done/conducted with descriptive technique. Pursuant to result of solution got the following node : belonging of middleman can arrest; detain goods ( retention rights), during fee, change fare not yet been paid by its him and the right to get released fare indemnation and fee it Obligation from middleman is to perform a jotter concerning him action as makelar ( Pasal 66, 67 Kitab Undang-Undang Hukum Dagang).
Keywords: rights, obligation of middleman, agreement of trade